Influence of Brand Image on The Purchase of Shampoo Products: Study on A Herbal Shampoo Product in Bandung City - Fabio Lazuardi; RD. Okky Satria; Rd. Rahadian Arby; Tini Supartini (Acman: Accounting and Management Journal, 2023)
This research was conducted with the aim of knowing and analyzing The Effect of Brand Image on The Purchase of Shampoo Products in one of the herbal shampoo products in The City of Bandung. The object of research was consumers of herbal shampoo products as many as 100 respondents, using descriptive analysis and verification analysis methods. Based on research using path analysis, it appears that the variable brand image on the purchase shampoo products at one of the herbal shampoo products in Bandung City is declared valid. The conclusions and suggestions that can be considered in connection with the research results are paying attention to Brand Image in order to increase the purchase of shampoo products.